Delve into the third dimension: Pertinence of 3D printing in forensic odontology - Alekhya Kanaparthi; Tejaswi Katne; Ramlal Gantala; Srikanth Gotoor (Wolters Kluwer Medknow Publications, 2020)
Three-dimensional (3D) printing is the forerunner in today's digital dentistry. It has revolutionized the field of healthcare and is making critical in roads today in forensics, driven primarily by its superior customization propensity. Application of this technique allows presentation of any evidence of human origin without any bias, with minimal degradation thereby reducing subjective errors. 3D printing has several applications, and this article is an attempt to enhance the knowledge of the forensic expert and to give an insight on its possible applications in forensic odontology.